Developing Digital Game E-Calf as Self-Directed Learning Media for the Third Grade Students of Elementary School at SD Lab Undiksha Singaraja - Sri Mahadewi, Ida Ayu; Mahayanti, I. A. N. W. S.; Utami, I. A. M. I. (LPPM Undiksha, 2018)
This study aimed at developing e – CALF as self directed – learning media for teaching English for third grade students of elementary school. This study was conducted at SD LAB UNDIKSHA Singaraja, in which the subjects of this study were the third grade students in III class. This study used ADDIE model. Since it is still a prototype media, there were only three procedure used namely Analysis, Design, and Develop. The data were collected by using observation sheet, teacher’s interview guide, students’ questionnaire, expert judgment rubric and syllabus analysis. The result of this research is a digital game media named e – CALF as self – directed learning media in form of application. The digital game of e – CALF consists of four topics namely part of body, days, school environment, and animals. To know the quality of the digital media, the result from expert judgments rubric was used. Based on the result of expert judgment rubric, it is find that the digital media of e – CALF is categorized as excellent digital game and also proper to use for learning English for third grade students.